External aid in elementary education: a double-edged sword - Ramachandran, Vimala (1999)
If externally-aided projects in elementary education remain outside the system, as they are tending to be, what purpose do they serve in the long run? Structures created to implement donor-aided projects should not be allowed to become contentious issues in educational administration. - Reproduced
Keywords: Education - India; Elementary education - India; Elementary education